Impact of the International Nosocomial Infection Control Consortium (INICC) Multidimensional Hand Hygiene Approach, over 8 years, in 11 cities of Turkey. Issue 4 (July 2015) - Leblebicioglu, Hakan; Koksal, Iftihar; Rosenthal, Victor D.; Akan, Özay Arıkan; Özgültekin, Asu; Kendirli, Tanil; Erben, Nurettin; Yalcin, Ata Nevzat; Ulusoy, Sercan; Sirmatel, Fatma; Ozdemir, Davut; Alp, Emine; et al.
Aims: To evaluate the effectiveness of the International Nosocomial Infection Control Consortium (INICC) Multidimensional Hand Hygiene Approach in Turkey and analyse predictors of poor hand hygiene compliance. Design: An observational, prospective, interventional, before-and-after study was conducted from August 2003 to August 2011 in 12 intensive care units (ICU) of 12 hospitals in 11 cities. The study was divided into a baseline and a follow-up period and included random 30-minute observations for hand hygiene compliance in ICU. The hand hygiene approach included administrative support, supplies availability, education and training, reminders in the workplace, process surveillance, and performance feedback. Results: We observed 21, 145 opportunities for hand hygiene. Overall hand hygiene compliance increased from 28.8% to 91% (95% CI 87.6–93.0, p 0.0001). Multivariate and univariate analyses showed that several variables were significantly associated with poor hand hygiene compliance: males vs. females (39% vs. 48%; 95% CI 0.79–0.84, p 0.0001), ancillary staff vs. physicians (35% vs. 46%, 95% CI 0.73–0.78, p 0.0001), and adult vs. pediatric ICUs (42% vs. 74%, 95% CI 0.54–0.60, p 0.0001). Conclusions: Adherence to hand hygiene was significantly increased with the INICC Hand Hygiene Approach. Specific programmes should be directed to improve hand hygiene in variables found to be predictors of poor hand hygiene compliance.